ACL Reconstruction: Is There A Difference In Graft Motion For Bone-patellar Tendon-bone Vs Hamstring Autograft At 6 Weeks Post-operatively?. Issue 7 (29th July 2014) - Irvine, James N.; Thorhauer, Eric; Abebe, Ermias Shawel; Tashman, Scott; Harner, Christopher D.
Objectives: Graft-tunnel healing following ACL reconstruction (ACLR) is a complex process influenced by multiple surgical variables, one of which is graft type. Clinical outcomes of bone-patellar tendon-bone (BTB) and hamstring (HS) autografts are similar, yet animal studies suggest that the healing processes may differ between the two autografts. Moreover, little is known about the relationship between graft-tunnel motion and the healing process in vivo in humans. This study was designed to compare BTB and HS graft motion within the femoral and tibial tunnels and the intra-articular graft post-operatively. We hypothesized that tunnel motion and mid-substance stretch would be greater for HS than BTB at 6 weeks following surgery. Methods: After IRB approval, 16 subjects (8 BTB, 8 HS) with an average age of 20 (range 16 to 37) underwent anatomic single-bundle ACLR by the same surgeon. Tunnel location, drilling and fixation were identical for all patients. Six 0.8 mm tantalum beads were embedded into ACL grafts prior to implantation using a custom injector. Pairs of beads were located within each bone tunnel and in the graft mid-substance (See image of graft constructs). Six weeks after surgery, CT scans were obtained and used to create 3D femur and tibia bone models. Cylindrical coordinate systems were fit to the bone tunnels to assess motion along tunnel axes. Dynamic stereo x-ray (DSX) images were collected at 100 frames/s while subjects performed treadmill walking and stair descent. Tibiofemoral kinematics were analyzed by combining the 3D models with DSX data. Graft-tunnel motion was defined as the maximum displacement of the implanted beads along the direction of the bone tunnel axis following footstrike. BTB and HS graft tunnel motions were compared using t-tests, with a significance level of p < 0.05. Results: Data are currently available for 6 BTB and 6 HS patients (N=12). Graft motion was seen in both groups within the femoral and tibial tunnels (range: 0.39 - 3.97 mm). Contrary to our hypothesis there was a trend towards greater femoral tunnel graft motion in the BTB relative to HS grafts during walking and stair descent (P=0.14 and 0.12, Table 1A-1B). There was more BTB graft motion in the femoral tunnel than in the tibial tunnel (significantly different for gait), and conversely more HS graft motion in the tibial tunnel than in the femoral tunnel (significantly different for stair descent). There was no detectable mid-substance stretch across all subjects. Conclusion: Six weeks following ACLR, less tunnel motion was expected for the BTB group compared to HS, due to the perceived advantages of bone-on-bone healing. However, more motion was observed for the BTB group within the femoral tunnel compared to HS, challenging the assumption that at 6 weeks after surgery there is greater graft-tunnel healing with BTB grafts. Based on previous studies, the native ACL elongates around 1-4% (0.3-1.2 mm) during loaded knee extension. At 6 weeks post surgery, it appears that the ACL grafts are moving in the tunnels rather than stretching in the mid-substance portion. This pattern may reverse over time, as graft-tunnel healing progresses (1-year followup testing is planned). Additionally, graft type appeared to affect the relative amount of motion between the tibial and femoral tunnels, though the cause and clinical significance of this finding is unclear. Results of this study could have important implications for graft selection, rehabilitation progression and return to sports.